Evaluation of the quality of life and risk of suicide - Alves, Verônica de Medeiros; Francisco, Leilane Camila Ferreira de Lima; Belo, Flaviane Maria Pereira; de-Melo-Neto, Valfrido Leão; Barros, Vinicius Gomes; Nardi, Antonio E. (Clinics, 2016)
OBJECTIVE: To identify the socio-demographic profiles, suicidal ideation, the presence of mental disorders and the quality of life of patients using mental health services in Arapiraca, Alagoas, Brazil. METHOD: Interviews were conducted in family health units and the Psychosocial Attention Center. The sample included 202 mental disorder patients with a risk of suicide attempts, 207 mental disorder patients without a risk of suicide attempts and 196 controls. This study used an identification questionnaire, the abbreviated World Health Organization Quality of Life questionnaire, Beck‘s Suicidal Ideation Scale and the Mini International Neuropsychiatric Interview. RESULTS: Patients who had a mental disorder and a risk of suicide attempts tended to be single, had less education and lower family income, were not working and showed lower scores in quality of life domains; 73 of these patients had suicidal ideation in the previous week. Depressive disorders, manic episodes, hypomanic episodes, social phobias, obsessive compulsive disorder, post-traumatic stress disorder, psychotic syndromes and generalized anxiety disorder were more frequent and statistically significant for patients at risk for suicide attempts. CONCLUSION: The management of patients with a risk of suicide attempts must focus on individual patients because this risk is directly linked to changes in quality of life and the improvement of these patients’ prognosis.